2022
DOI: 10.24203/ajafs.v10i5.7055
|View full text |Cite
|
Sign up to set email alerts
|

Rice Production Technology Improvements for Higher Productivity Along with the Sustainable Agriculture Process in the Mekong Delta

Abstract: This study examines sustainable agricultural development in the Mekong Delta, Vietnam by focusing on technology improvement for minimizing the environmental load in rice production with sufficient yield and quality.  Among rice-producing countries, Vietnam is the third-largest rice export country worldwide. High-yield rice production is still a critical issue in Vietnam. However, in recent years, quality improvement and low environmental load agriculture have been fundamental issues.   In this research, we con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
0
0
Order By: Relevance
“…Unsuitable cropping conditions and inappropriate land may lead to lower yields and emissions (e.g., in Haikou). Studies in the tropics have shown that high yield depends on a combination of factors; simply increasing inputs may not offset yield declines due to environmental changes (Kontgis et al., 2019; Matsubara et al., 2022). To address food security and climate change challenges in Hainan, increasing the rice planting area in regions with higher yields and lower CFa values (e.g., in Lingao and Tunchang) could represent a solution.…”
Section: Discussionmentioning
confidence: 99%
“…Unsuitable cropping conditions and inappropriate land may lead to lower yields and emissions (e.g., in Haikou). Studies in the tropics have shown that high yield depends on a combination of factors; simply increasing inputs may not offset yield declines due to environmental changes (Kontgis et al., 2019; Matsubara et al., 2022). To address food security and climate change challenges in Hainan, increasing the rice planting area in regions with higher yields and lower CFa values (e.g., in Lingao and Tunchang) could represent a solution.…”
Section: Discussionmentioning
confidence: 99%